2013
DOI: 10.1111/exd.12292
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory peeling skin syndrome caused by homozygous genomic deletion in the PSORS1 region encompassing the CDSN gene

Abstract: Peeling skin syndrome (PSS) type B is a rare recessive genodermatosis characterized by lifelong widespread, reddish peeling of the skin with pruritus. The disease is caused by smallscale mutations in the Corneodesmosin gene (CDSN) leading to premature termination codons. We report for the first time a Japanese case resulting from complete deletion of CDSN. Corneodesmosin was undetectable in the epidermis, and CDSN was unamplifiable by PCR. QMPSF analysis demonstrated deletion of CDSN exons inherited from each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…Clinically, there are four main types of EB: EB simplex (EBS), caused by mutations in 14 different genes; junctional EB (JEB), now known to be caused by mutations in eight different genes; dystrophic EB (DEB), caused by mutations in collagen 7A1 (COL7A1); and Kindler syndrome, caused by mutations in FERMT1 (Table ). We included two genes listed for convenience under the EBS subtype, carbohydrate sulfotransferase 8 (CHST8) and corneodesmosin (CDSN), because they have been reported in fragile skin syndromes. The 2014 EB classification lists only 11 genes for EBS .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically, there are four main types of EB: EB simplex (EBS), caused by mutations in 14 different genes; junctional EB (JEB), now known to be caused by mutations in eight different genes; dystrophic EB (DEB), caused by mutations in collagen 7A1 (COL7A1); and Kindler syndrome, caused by mutations in FERMT1 (Table ). We included two genes listed for convenience under the EBS subtype, carbohydrate sulfotransferase 8 (CHST8) and corneodesmosin (CDSN), because they have been reported in fragile skin syndromes. The 2014 EB classification lists only 11 genes for EBS .…”
Section: Introductionmentioning
confidence: 99%
“…We found five cases3,17,22,29,31 in which there were additional VUCS in the same causative gene. There were five cases5,10,15,23,30 in which there were two homozygous or compound heterozygous VUCS in fragile skin genes other than the causative gene. There were also…”
mentioning
confidence: 99%
“…Type B may also be associated with several noncutaneous anomalies and various abnormal laboratory findings. In type B PSD, ultrastructural features of corneodesmosomes and skin separation recapitulated those in the CDSN knock-out mice [30]. Dominant nonsense mutations in CDSN that produce a truncated form of CDSN underlie hypotrichosis simplex of the scalp, a rare disease that leads to complete baldness in young adults [32].…”
Section: Corneodesmosin Peeling Skin Disease Type B and Hypotrichosismentioning
confidence: 79%
“…Next in human studies, type B peeling skin disease (PSD) was found to be caused by the absence of functional corneodesmosin expression (Table 1, Fig. 2) [29,30]. PSD is a rare autosomal recessive genodermatosis characterized by continuous superficial exfoliation of the outer epidermis.…”
Section: Corneodesmosin Peeling Skin Disease Type B and Hypotrichosismentioning
confidence: 99%
“…Thus, the loss of functional PSORS1C2 in cetaceans is in line with the loss of this programme. In humans, homozygous deletions of six different genes including CDSN and PSORS1C2 are associated with generalized peeling skin disease . As the inactivation of CDSN alone is sufficient to induce peeling skin disease, these clinical cases are not informative about the role of PSORS1C2 , as the latter may be obscured by the effects of lack of CDSN .…”
Section: Discussionmentioning
confidence: 99%